92 Fumarate Hydratase-Deficient Renal Cell Carcinoma: Aspiration and Effusion Cytologic Features. (11th January 2018) - Shyu, Irene; Wang, Xiaoyan; Robila, Valentina; Mehra, Rohit; McHugh, Jonathan; Chen, Ying-Bei; Udager, Aaron; Gill, Anthony; Cheng, Liang; Amin, Mahul; Smith, Steven
Abstract: Fumarate hydratase-deficient renal cell carcinoma (FH-deficient RCC) is a rare, highly aggressive renal cell carcinoma (RCC), thought to arise mostly in the setting of hereditary leiomyomatosis-renal cell carcinoma syndrome (HLRCC) with germline mutation of fumarate hydratase (FH). Due to the aggressiveness of these tumors and frequent lack of ascertainable family history, these tumors may first present as metastases, which may be sampled for cytology. Nonetheless, cytologic features of FH-deficient RCC have not been reported. Herein, a total of eight cytologic samples from seven patients (two women and five men, 25–69 years old) with confirmed FH-deficient RCCs were identified and evaluated retrospectively. Cytology samples included three cases of malignant effusions (one pleural and two ascites), two direct renal aspirates, and one each aspirates of supraclavicular node, liver metastasis, and pleural/chest wall metastasis. Cytologic preparations were generally sparsely cellular but with striking, markedly enlarged malignant cells, presenting as small clusters and abortive papillae in a hemorrhagic and inflammatory background. Individual cells showed markedly enlarged, pleomorphic nuclei with prominent or macronucleoli and moderate amount of cytoplasm. On Diff-Quik-stained smears and cell blocks, cytoplasmic vacuolation, ranging from delicately flocculent to bubbly or vacuolated, was visible. Prominent, inclusion-like nucleoli with perinucleolar halos (hallmark of FH-deficient RCC) were visible, focally in every case, particularly on Pap stain and H&E cell block sections. In conclusion, in cytologic preparations, rudimentary features characteristic of FH-deficient RCC may be identified. While identified retrospectively here, we argue that with appropriate clinical correlation, especially with ascertainment of any syndromal stigmata as context, the cytomorphology is sufficiently distinctive to trigger recognition and confirmatory workup for this aggressive variant.